Corporate governance and operations performance: inventory study on Malaysian listed firms - Nadarajan, Santhirasegaran; Chandren, Sitraselvi; Bahaudin, Ahmad Yusni; Mohamed Elias, Ezanee; Mohd Nawi, Mohd Nasrun (ExcelingTech Publishers, 2015)
This paper reveal the relationship by developing a conceptual model that entails the relationship between corporate governance and operations performance from the angle of inventory management that’s include inventory value, inventory turnover and days of supply as the performance measure. This study makes a difference from the other studies which are focused on using accounting measures to see if corporate governance affect the firm’s performance but this study will discuss on using inventory measures that will dictates the earlier study.The finding of this study reveals that corporate governance mechanisms have an impact on inventory decision directly affect the operations performance.